Patterns and correlates of sexual activity and condom use behavior in persons 50-plus years of age living with HIV/AIDS. - Lovejoy, Travis I; Heckman, Timothy G; Sikkema, Kathleen J; Hansen, Nathan B; Kochman, Arlene; Suhr, Julie A; Garske, John P; Johnson, Christopher J (AIDS and behavior, 2008)
This study characterized rates of sexual activity and identified psychosocial and behavioral correlates of sexual activity and condom use in a metropolitan sample of 290 HIV-infected adults 50-plus years of age. Thirty-eight percent of participants were sexually active in the past three months, 33% of whom had at least one occasion of anal or vaginal intercourse that was not condom protected. Rates and correlates of sexual activity and condom use differed between gay/bisexual men, heterosexual men, and heterosexual women. In the past three months, 72% of heterosexual men were sexually active compared to only 36% of gay/bisexual men and 21% of heterosexual women. However, among sexually active persons, only 27% of heterosexual men reported inconsistent condom use compared to 37% of gay/bisexual men and 35% of heterosexual women. As the number of older adults living with HIV/AIDS in the U.S. continues to increase, age-appropriate secondary risk-reduction interventions are urgently needed.
Keywords: Bisexuality; Computers; Condoms; Female; Heterosexuality; HIV Infections; Homosexuality, Male; Humans; Interviews as Topic; Male; Middle Aged; New York City; Ohio; Psychology; Questionnaires; Self Disclosure; Sexual Behavior; Sexual Partners